The CYCLOIDEA-RADIALIS module regulates petal shape and pigmentation, leading to bilateral corolla symmetry in Torenia fournieri (Linderniaceae) - Su, Shihao (The New phytologist, 2017)
© 2017 Sun Yat-sen University New Phytologist © 2017 New Phytologist Trust.